Merchantable wood volume response of P. radiata D. Don post thinned plots on coated and uncoated urea fertilizers - Nirola, R.; Saint, C.; Hehir, J. O.; Liu, J. (Banko Janakari, 2020)
Our study was focused on whether the optimization of nutrition at various growth stages of Pinus radiata D. Don plantation was an important factor to increase its merchantable wood volume yield in Silviculture. The present study site is located within the ‘Green Triangle’ bordering the Australian states of South Australia and Victoria. A total of 24 sampling sub-plots, averaged to 12 super plots, were established in both the sites, and all the plots, except one set aside as 'controlled plot' in each site, were treated with 5 types of coated and un-coated urea fertilizers. The data on tree-height and diameter at breast height over bark (DBHOB) of all the standing trees were measured and recorded. A five-year sampling data from the 24 sub-plots consisting of two sites, namely Picks (Site 'A') and Hollands Lane (Site 'B') in post thinned condition were analysed. The specific target was to evaluate a productivity response in terms of merchantable volumes based on fertilizer types. The statistical analysis employing ANOVA, t-test, a neural network model, decision tree and box-plot model based on fertilizer treatment determined that Di-Ammonium Phosphate Entec Urea (DAPEU) fertilizer was found to be more effective in increasing productivity. As such, the merchantable wood volume increments measured after four years of application of DAPEU were found to be 48.61 m3 ha-1 at Site 'A' and 41.97 m3 ha-1 at Site 'B', higher than the 46.71 m3 ha-1 at Site 'A' and 39.79 m3 ha-1 at Site 'B' with 'control' treatment. Hence, the application of DAPEAU was found to be effective as compared to the 'control' treatment in silviculture to increase the merchantable wood volume.